Organic chemistry - McMurry, John (Brooks/Cole-Thomson Learning, 2004)
This undergraduate textbook describes the chemical structure of specific families, beginning with the simple alkenes and progressing to the more complex aromatic compounds, alcohols, ethers, carbonyl compounds, and biomolecules. The sixth edition replaces the previously supplied CD-ROM with a web site for creating a personalized study plan.